O impacto do crédito rural sobre a produtividade : uma análise para os municípios brasileiros - Mello, Cristine Ramos de (2016)
The agricultural policy grounded in subsidized financing suffers challenges for disparate reasons over time. Research on credit differ on the results, suggesting that the impact will occur as a result of market development and its concentration. This problem is also seen when exploring the Rural Credit across Brazil. The main references have divergent results, which confirm, in general, the present controversy in the Brazilian literature on the relevance and effectiveness of the Rural Credit. This research has as main aim to understand how rural credit lines impacting productivity in Brazilian agriculture. Construction of the survey data were collected with the Central Bank and the Brazilian Statistical Bureau, the volumes and contract numbers for municipalities and area harvested and planted, in addition to the financial outcome in the different municipalities. Thus, it was possible to establish the financial productivity by municipality over Brazil. They were tested, following 12 models, four for productivity temporary crops, four for permanent crops and four for overall productivity. The independent variables were the credit volumes and the number of contracts in its three modes: cost, investment and marketing. They were also tested these same variables in their quadratic terms and lagged in one to two years, since the sample was annual, thus forming a data panel for ten years in the period 2003-2012, to 5,460 municipalities. The volume contracted for cost and investment were relevant to the explanation of financial productivity in various measures: temporary crops, permanent crops and total crops in all models. Other variables shows to be important as the models varied. The results also confirm the credit dynamic spreading over time for the variables financial volume of cost and financial volume of investment in the period of one year. The number of contracts for cost also has significant effects for the following crop. In particular, the number of funding agreements was significant for up to two years to total and permanent crops of agriculture.